2022
DOI: 10.21203/rs.3.rs-2046453/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microfabricated Polymer-Metal Biosensors For Multifarious Data Collection From Electrogenic Cellular Models

Abstract: Benchtop tissue cultures have become increasingly complex in recent years, as more “on-a-chip” biological technologies such as Microphysiological Systems (MPSs) work to incorporate cellular constructs that more accurately represent their respective biological systems. Such MPSs have begun providing major breakthroughs in biological research and are poised to shape the field in the coming decades. These biological systems necessitate integrated sensing modalities to procure complex, multiplexed datasets, with u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…[17][18][19]34,[58][59][60][61] However, the most common approaches toward the cell-to-culture ware interface impedimetric sensing target involve cell contact or motile ability. [47,62,63] One example is Rapier et al reported a simple and intrinsic microfluidic sensory system based on impedimetric sensing for determining cell location and confluency. [23] The developed method was integrated with four bands of gold electrodes spanning the width of 500-μm-widemicrofluidic channels.…”
Section: Electrical Sensormentioning
confidence: 99%
“…[17][18][19]34,[58][59][60][61] However, the most common approaches toward the cell-to-culture ware interface impedimetric sensing target involve cell contact or motile ability. [47,62,63] One example is Rapier et al reported a simple and intrinsic microfluidic sensory system based on impedimetric sensing for determining cell location and confluency. [23] The developed method was integrated with four bands of gold electrodes spanning the width of 500-μm-widemicrofluidic channels.…”
Section: Electrical Sensormentioning
confidence: 99%